Antidiarrheal Activity of Dissotis multiflora (Sm) Triana (Melastomataceae) Leaf Extract in Wistar Rats and Subacute Toxicity Evaluation. (5th November 2017) - Afagnigni, Alian Désiré; Nyegue, Maximilienne Ascension; Ndoye Foe, Chantal Florentine; Njankouo Ndam, Youchahou; Njayou, Frédéric Nico; Fonkoua, Marie Christine; Etoa, François-Xavier
Abstract : The present work was undertaken to evaluate antidiarrheal activity of ethanolic leaf extract of Dissotis multiflora (Sm) Triana (D. multiflora) on Shigella flexneri -induced diarrhea in Wistar rats and its subacute toxicity. Diarrhea was induced by oral administration of 1.2 × 10 9 cells/mL S. flexneri to rats. Antidiarrheal activity was investigated in rats with the doses of 111.42 mg/kg, 222.84 mg/kg, and 445.68 mg/kg. The level of biochemical parameters was assessed and organs histology examined by 14 days' subacute toxicity. S. flexneri stool load decreased significantly in dose-dependent manner. The level of ALT increased (p < 0.05 ) in male rats treated with the dose of 445.68 mg/kg while creatinine level increased in rats treated with both doses. In female rats, a significant decrease (p < 0.05 ) of the level of AST and creatinine was noted in rats treated with the dose of 222.84 mg/kg of D. multiflora . Histological exams of kidney and liver of treated rats showed architectural modifications at the dose of 445.68 mg/kg. This finding suggests that D. multiflora leaf extract is efficient against diarrhea caused by S. flexneri but the treatment with doses lower than 222.84 mg/kg is recommended while further study is required to define the exact efficient nontoxic dose.